Flow in experimental berry aneurysms: method and model. - Kerber, C W; Heilman, C B (American Journal of Neuroradiology, 1983)
This study addresses two basic questions: What are the flow dynamics in aneurysms? Can these flows be modified to enhance retention of adhesive? Using Pyrex glass bifurcations, fluid flow was studied in a variety of aneurysms placed at varying positions around the bifurcations. Indicators injected into the slipstreams were recorded and studied both by stop-frame high-speed movie analysis and with 35 mm slides. Even at low-flow rates, a central slipstream strikes the apex of bifurcations, and may be partly responsible for the initial production of berry aneurysms. A low-pressure zone occurs at the lateral angle of bifurcations, probably explaining the formation of endovascular cushions. Flow into symmetrically placed narrow neck aneurysms did not occur. Indicator entered the aneurysm in a turbulent fashion only when there was orifice (lip) asymmetry. Both lip asymmetry and rapid flow favor intraaneurysmal turbulent flow.